(untitled) (Indian Journal of Animal Production and Management, 2024)
The bioactive components refer to compounds either naturally existing in food or introduced during food processing that may have physiological and biochemical functions when consumed by humans and have crucial impacts on human metabolism and beneficial effects on human health, that guard neonates and adults against pathogens and illnesses and Antioxidants may positively affect human health by protecting the body against damage caused by reactive oxygen species, which attack membrane lipids, protein and DNA. Bioactive components encompass proteins, peptides, carbohydrates, lipids, glycolipids and other minor biomolecules i.e. vitamins, lactoferrin, enzymes, immunoglobulin and growth factors. The present study was conducted on fatty acids in milk of various indigenous cattle breeds viz. Kankrej, Sahiwal and Rathi. For fatty acids, 36 milk samples (12 from each breed) were collected from different Livestock Research Station, Bikaner. Fatty acids were measured by GC-MS. The analysis of variance revealed monounsaturated fatty acids and Poly unsaturated fatty acids significantly differed in different indigenous cattle breeds whereas saturated fatty acids did not differ. The present study concluded that the milk from the indigenous cattle breeds viz. Kankrej, Sahiwal, and Rathi have distinct compositions and quantities of different active components which can be harnessed for the promotion of different functional foods based on indigenous cattle milk and further pharmaceutical preparations can be promoted for the benefit of farmers and entrepreneurs.